Lectura publică în epoca Facebook: Maria Pilchin, critic literar, cercetătoare - admin, admin (BIBLIOPOLIS, 2023)
In the digital or the media age, as it is called today, we have the feeling that we are populating an artificial Paradise. Some critical voices insist on the idea that it is just a great virtual Babylon in which we live a decadence of everything that means classical, logocentric, Christian culture, everything that represented the western culture of the last two millennia. Others talk about progress, modernization, innovation through the new paradigms of a new human age. In the context of the economy of attention, libraries are the institutions that facilitate the meeting between the user and the library services, in general, and the reader and the book, in particular. Reading education and reading culture certainly remain the strategic directions of a library. Thus, we explain the increased interest in digital platforms and social networks in the online environment where various events dedicated to reading can occur.